Pengaruh Pembelajaran Kitab Akhlak Lil Banin terhadap Etika Santri Madrasah Diniyah Al-Furqon di Pondok Pesantren Darul 'Ulum Rejoso Peterongan Jombang - Muhtadi Muhtadi; Agus Ainul Yaqin (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2018)
This study aims to find out how far the influence o of the learning of Akhlaq Lil Banin Book on the ethics of santri Diniyah Al-Furqon School in Darul 'Ulum Islamic Boarding School Rejoso Peterongan Jombang. This type of research is quantitative, with a population of 150 students, consisting of 54 class I students, 50 class II students and 46 class III students. The sample was taken 20% of the total population, namely 30 santri. The data collection technique uses observation, interview, questionare and documentation techniques. While the data analysis techniques use the product moment correlation formula as follows: From the results of the study, it can be concluded that the influence of the learning of Akhlaq Lil Banin Book on the ethics of santri Diniyah Al-Furqon School in Darul 'Ulum Islamic Boarding School Rejoso Peterongan Jombang is 30.36% or 0.402% (strong enough) and the remaining 69.64% is influenced by other factors. Based on the results of the study, the teacher is expected to be a role model for the students because what is done by the teacher will be a reflection of ethics / morals for students in everyday life.